Coefficient Bounds for Certain Subclass of Analytic Functions Defined By Quasi-Subordination - Juma, Abdul Rahman S.; Saloomi, Mohammed H. (Iraqi Journal of Science, 2018)
In this paper, we define certain subclasses of analytic univalent function associated with quasi-subordination. Some results such as coefficient bounds and Fekete-Szego bounds for the functions belonging to these subclasses are derived.